SARS-CoV-2 contamination potential in environmental and wastewaters in the Algarve region, Southern Portugal - Galvão, Helena M.; Mendes, Pedro J.; Figueiredo, Aida; Santos, Ricardo; Monteiro, Silvia (Frontiers in Water, 2022)
The Ria Formosa, Southern Portugal (Algarve) is a mesotidal lagoon with restricted exchange with Atlantic Ocean. Due to arid Mediterranean climate and absence of freshwater inputs, the lagoon remains hypersaline relative to open coastal waters (> 37 psu). Generally, fecal coliforms and other allochthonous land-derived bacteria do not survive long in seawater due to UV, osmotic shock, oligotrophy and competition with marine bacteria. However, survival of human pathogenic viruses in natural waters remains relatively unknown. In view of 2020-2021 SARS-CoV-2 pandemic, this study aimed to estimate potential contamination by wastewater and persistence in marine environment. Five sampling campaigns were carried out in 2020 and 2021 at three stations in the Ria Formosa, as well as affluent and effluent from three wastewater treatment plants. Despite high fecal contamination at lagoon stations, SARS-CoV-2 could not be detected using improved methodology. Raw wastewaters were positive at Faro-Aeroporto 21/10/2020, 14/12/2020, 08/03/2021; Vilamoura 21/10/2020, 14/12/2020; Olhão 14/12/2020. All treated wastewaters were negative, as well as environmental samples. Highest viral titers were observed in Faro-Aeroporto untreated wastewater on 8/03/2021 (1.35 x105 genomic copies L-1) coinciding with peak SARS-CoV-2 cumulative positive cases in Algarve, namely 2.03 x104, yet SARS-CoV-2 could not be detected in Vilamoura and Olhão untreated wastewater on that date. Thus, the contamination potential of SARS-CoV-2 remained very low or non-existent in this coastal lagoon during pandemic surges in Southern Portugal. However, predicted climate change in the Algarve region and its impact on microbial populations remains to be addressed by both health and tourist authorities.